Impact of Psychiatric Nurse-Led Programs on Self-Care Practices, Medication Adherence, and Psychological Health in Schizophrenia Patients: A Mixed-Methods Investigation of Caregiver Experiences - Palani Subbiah; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Venkatesh Mathankumar; Anbalagan Marudan; Gayathri Karunakaran; Kala Paramasivam (Journal of Pharmacy and Bioallied Sciences)
Introduction: Schizophrenia affects approximately 20 million people worldwide, where social dysfunction is significant along with burdening the care giver. Effective intervention is critical to enhance self-care, medication adherence, and psychological well-being. Materials and Methods: This mixed-method study used an explanatory sequential design with 60 caregivers at Institute of Mental Health, Chennai. Psychoeducation, breathing exercises, and relaxation techniques formed the intervention strategy, while data were obtained through a variety of scales. Results: The intervention improved significantly in self-care (from 77.50 to 86.17), medication compliance (from 3.05 to 4.48), and psychological well-being (from 67.68 to 76.42). The qualitative themes included caregiver empowerment. Conclusion: The intervention has enhanced caregiver outcomes; hence, it can be incorporated into psychiatric care. Future studies should explore the long-term effects.